2013
DOI: 10.1002/micr.22150
|View full text |Cite
|
Sign up to set email alerts
|

Spinal reconstruction for osteomyelitis with free vascularized fibular grafts using intra‐abdominal recipient vessels: A series of three cases

Abstract: Reconstruction of bony defects in the surgical management of vertebral osteomyelitis is a challenging endeavor. Our objective is to report the use of intra-abdominal vessels as the recipient vessels for microanastomosis of vascularized bone graft and the use of a spinal cage for fixation. Three patients failed conservative treatment for vertebral osteomyelitis and suffered pathologic fracture. Their treatment consisted of staged posterior irrigation and debridement with segmental fixation, followed by a thorac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 34 publications
0
11
0
1
Order By: Relevance
“…FVFBGs have been reported for a variety of spinal conditions including osteomyelitis, neoplasms, neurofibromatosis, and Arnold-Chiari malformations 2 3 5 6 15) . Winters et al 23) reported a case series of 30 spine patients with FVFBGs.…”
Section: Discussionmentioning
confidence: 99%
“…FVFBGs have been reported for a variety of spinal conditions including osteomyelitis, neoplasms, neurofibromatosis, and Arnold-Chiari malformations 2 3 5 6 15) . Winters et al 23) reported a case series of 30 spine patients with FVFBGs.…”
Section: Discussionmentioning
confidence: 99%
“…There are different reports using the free fibula flap for reconstruction of multilevel spine defects both for anterior spinal fusion, posterior fusion, osteomyelitis, or in irradiated patients . The benefits of using a fibula flap include a consistent anatomy, relative ease of flap harvest, length of pedicle, and low donor‐site morbidity.…”
Section: Discussionmentioning
confidence: 99%
“…39 In spinal reconstruction, popular options include pedicled vascularized ribs, iliac crest, and, most commonly, FVFGs. 43 FVFGs rely on the peroneal artery as a donor vessel, 44 and recipient vessels vary depending on the region of reconstruction-internal thoracic vessels, lumbar segmental vessels, iliac vessels, inferior mesenteric vessels, and the aorta are common choices. 43 Advantages of the FVFG include sufficient length to cover larger defects and a larger amount of cancellous bone leading to the quick and high union rates reported.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…43 FVFGs rely on the peroneal artery as a donor vessel, 44 and recipient vessels vary depending on the region of reconstruction-internal thoracic vessels, lumbar segmental vessels, iliac vessels, inferior mesenteric vessels, and the aorta are common choices. 43 Advantages of the FVFG include sufficient length to cover larger defects and a larger amount of cancellous bone leading to the quick and high union rates reported. 45 The use of VBG in cases of tissue bed compromise (deep space infection, osteomyelitis, radiation) has been described in several reasonably sized case series.…”
Section: Systematic Reviewmentioning
confidence: 99%